Relationship between dysfunctional attitudes and level of digital addiction in young adults - Ercan, Feride; Erdoğan, Senanur; Erlen, Cansu; İnce, Dilanur; Demirci, Esma; Alan, Nursel (Journal of Dependence, 2023)
Objective: The aim of the study to examine the relationship between dysfunctional attitudes and the level of digital addiction in young adults.Method: The sample of the study consisted of n=390 young adults between the ages of 18-24, reached by random sampling method, which is one of the non-probability sampling methods. As a data collection tool; “Participant Information Form”, “Dysfunctional Attitude Scale (DAS-17)” and “Digital Addiction Scale (DAS)” were used. The data of the research was obtained with an online questionnaire prepared through Google Forms.Results: The mean age of the participants was 20.93±1.60 (min.=18.0; max.=24.0) and 83.8% were women. The mean total score of the young adults was 53.47±19.32 for the Dysfunctional Attitude Scale and 2.79±0.82 for the Digital Addiction Scale. A positive and moderate relationship was found between the participants' total mean scores obtained from Dysfunctional Attitude Scale and Digital Addiction Scale. The linear regression model established with the variables of the descriptive characteristics of the participants, their characteristics related to internet use, their dysfunctional attitudes and digital addiction levels was found to be statistically significant, and it was determined that the model explained 33.7% of the variance.Conclusion: Digital addiction in young adults can be explained by having dysfunctional attitudes, education level, daily internet usage time and not having an additional chronic disease. This research can help to understand the factors that influence digital addiction and provide evidence for developing preventive and intervention strategies specific to young adults.
Keywords: Young adults; dysfunctional attitudes; digital addiction